Multiproxy records of Holocene millennial‐scale climatic variations from the aeolian deposit in eastern Horqin dune field, northeastern China. (27th March 2018) - Liu, Bing; Jin, Heling; Sun, Liangying; Niu, Qinghe; Zhang, Caixia; Xue, Wenping; Liu, Zhengyu
Abstract : The record of the Holocene millennial‐scale climate variations from the aeolian deposit around the monsoonal boundary zone in northern China is poorly understood because the desert sediments are usually scattered and geological archives are discontinuous. Here, we conducted magnetic, sedimentological, and geochemical analyses of the palaeosol‐aeolian sand sequence from the eastern Horqin dune field in northeastern China, which documented the detailed history of climatic variations during the past 7.0 ka. The results indicate that the climate became more humid around 7.0−5.0 ka and approached an optimal humid condition around 5.0–3.6 cal ka BP. Afterward, the moisture condition clearly declined in 3.6–1.3 cal ka BP and was replaced by dry climate at the end. Additionally, we discovered that 10 periodically dry events that punctuated the overall pattern of climatic variations in the region, with times of more than 7.0, 5.7–5.5, 5.5–5.0, 4.6–4.2, 4.2–3.7, 3.6, 3.5–3.3, and 1.3 cal ka BP. These intervals were not only very consistent with the dry/cold events in the monsoonal boundary zone of northern China, owing to weak summer monsoonal strength forced by solar radiation, but were also accordant with the increased Asian winter monsoon strengths induced by environment variations of the high latitude area. This phenomenon probably implies the antiphase relationship between Asian summer and winter monsoons on the Holocene millennial‐scale around the monsoonal boundary zone of northern China.